BEBAN KERJA DAN KESEIMBANGAN KEHIDUPAN KERJA AKUNTAN - Suhayati, Ely; Najwa Alia Putri (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
This study intends to investigate the impacts of workload on work-life balance and accountants' performance, as well as the impact of work-life balance on performance. Using a descriptive-verificative method and Structural Equation Modeling via SmartPLS 4.0, the research involves 173 respondents from 79 public accounting firms in Indonesia. The results show that workload significantly affects WLB, depending on the ability to manage tasks effectively. WLB strongly impacts accountants’ performance, highlighting the need to harmonize career and lifestyle without compromising well-being. Additionally, workload directly influences performance, underscoring the importance of managing workload to sustain health and deliver quality audits. This study aims to prepare alumni both in Indonesia and outside Indonesia to achieve balance in their personal and professional lives, contributing to a healthier and more productive generation, thus producing optimal performance.